2018
DOI: 10.1002/jum.14879
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Conventional Ultrasound Characteristics of Breast Tumors With Axillary Lymph Node Metastasis and Ki‐67 Expression in Patients With Breast Cancer

Abstract: Objectives-To explore the association between the ultrasound (US) characteristics of breast tumors with axillary lymph node metastasis (ALNM) and Ki-67 expression in patients with breast cancer.Methods-In total, 527 consecutive patients with breast cancer who had undergone US examinations and curative surgery with axillary lymph node evaluations were included. The size, shape, aspect ratio, margin, internal echo, internal calcification, posterior echo attenuation, lymphatic hilar structure, cortical thickness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
(38 reference statements)
6
22
1
Order By: Relevance
“…To the Editor : We are very grateful to you for your invitation and for Dr Altundag's comments. We feel very honored to know that “Correlation of Conventional Ultrasound Characteristics of Breast Tumors With Axillary Lymph Node Metastasis and Ki‐67 Expression in Patients With Breast Cancer” has been published online in Early View of the Journal of Ultrasound in Medicine . Here, we will elaborate Dr Altundag's question from 2 aspects as follows.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…To the Editor : We are very grateful to you for your invitation and for Dr Altundag's comments. We feel very honored to know that “Correlation of Conventional Ultrasound Characteristics of Breast Tumors With Axillary Lymph Node Metastasis and Ki‐67 Expression in Patients With Breast Cancer” has been published online in Early View of the Journal of Ultrasound in Medicine . Here, we will elaborate Dr Altundag's question from 2 aspects as follows.…”
supporting
confidence: 88%
“…First, it was a pity that we did not take triple‐negative breast cancer into consideration; however, triple‐negative breast cancer was not the focus of our study. The sentence “Triple‐negative breast cancer patients with high expression of Ki‐67 were expected to have more tendency for ALNM,“ instead of being the conclusion of the study, was actually our own point of view. The Ki‐67 protein, a nonhistone nuclear protein, is exclusively related to cell proliferation.…”
mentioning
confidence: 99%
“…In intraoperative ultrasonography (IOUS), Baskan et al (23) found that the pathogenicity of the solid parts, margins, and contours of glioma were related to the level of Ki-67. Zhang et al (24) discovered that breast cancer with heterogeneous internal echo had stronger proliferative ability and poor prognosis. Compared with other studies, in addition to the differences in tumor types, the constituent cells of different subtypes of STS are diverse.…”
Section: Discussionmentioning
confidence: 99%
“…A cortical thickness of greater than 3 mm is associated with more than three-fold increase in metastatic disease, loss of fatty hilum is associated with a 27-fold increase, and tumor margin irregularity is associated with a 3-fold increase. 38 , 39 Lymph node diameter greater than 10 mm is also associated with increased risk of metastatic disease. While these features have high odds ratios, individually they have poor AUC in predicting the presence of metastatic disease.…”
Section: Axillary Ultrasoundmentioning
confidence: 99%